2012
DOI: 10.18517/ijaseit.2.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic System for Slope Stability Prediction

Abstract: The main goal of this research is to predict the stability of slopes using fuzzy logic system. GeoStudio, a commercially available software was used to compute safety factors for various designs of slope. The general formulation of the software could analyze slope stability using various methods of analysis i.e. Morgenstern-Price, Janbu, Bishop and Ordinary to calculate the safety factors. After analyzing, fuzzy logic was used to predict the slope stability. Fuzzy logic is based on natural language and concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The finding has shown that ANFIS could predict a high precision safety factor compared to others including the Artificial Neural Network technique. ANFIS predict show the safety factor with the higher accuracy and nearest to the targeted accuracy [19]. In the future, the other techniques could be explored such as Support Vector Machines (SVM) towards determining the significant prediction on the slope stability measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The finding has shown that ANFIS could predict a high precision safety factor compared to others including the Artificial Neural Network technique. ANFIS predict show the safety factor with the higher accuracy and nearest to the targeted accuracy [19]. In the future, the other techniques could be explored such as Support Vector Machines (SVM) towards determining the significant prediction on the slope stability measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the sharing proportions between the use of the electric braking and the mechanical braking in this regenerative-plugging method, the fuzzy-logic control (FLC) theory is considered [16]. It enables to adjust the speed, the state-of-charge SoC of the battery, and the required braking torque.…”
Section: E Braking Methodsmentioning
confidence: 99%
“…This paper proposes a simple but effective technique to deal with the problems found so far in the regenerative braking implementation. The fuzzy-logic theory [16] is implemented to automatically control the proportion distribution of regenerative and electric brakings through one single brake-lever. To improve the current response of electric braking, the proportional-integral control method is used.…”
Section: Introductionmentioning
confidence: 99%
“…Karaman (2013) and Karaman et al (2013) utilized the Slope Stability Probability Classification (SSPC) system (Hack, 1998) and determined the maximum slope height for design of safe slopes using current height of slopes as an input parameter. Mohamed et al (2012) performed the fuzzy logic method for the investigation of slope stability and pointed out that the slope height is one of the most significant input parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Slope height is a significant parameter used in the limit equilibrium (Kesimal et al, 2008), numerical analyses (Kadakçı Koca and Koca, 2014), some rock mass classification systems (Karaman et al, 2013;Karaman, 2013) and fuzzy logic system (Mohamed et al, 2012). Kadakcı Koca and Koca (2014) mentioned that slope angle, water saturation, seismic force and slope height are the important parameters that affect the stability of the slopes.…”
Section: Introductionmentioning
confidence: 99%